(3MhGTi CHj eMeO YHO Gddg Hf HQi Ydi GdeYQHs - (3CHh efUhQ ehghH Hf CMeO Hf eMeO Hf GdNVQ Hf GdMSf GdLhGdjbi,J (B539 (3g` s ((3eMeO Hf YHO Gdedc Hf YSGcQ GdTGaYi GdHYdHci s)
(3ChdgG (B:s
(3gPG eG CNP hGSJOQcI CHh eMeO YHO Gddg Hf HQi GdebOSi GdfMhi Ydi cJGH TjNfG CHj efUhQ ehghH Hf CMeO GdLhGdjbi GdehShe HcJGH eG YQHJg GdYQH ef GdcdGe GdCYLei hZjQg ENJUQJ GdMhGTi Ohf ZjQgG ef fU GdcJGH s
(3BNQgG (B:s
(3bGd dHjO (B: (3hdYdgG fjb bjGe Mhdge cd edKhe EPG UH ged BNQ eG PcQ GdTjN CHh eMeO Hf HQi hGdMeO ddg hMOg s
(3hGdeLehYI ef cJH GdCejQ RjOGf Hf CMeOs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(772/5) s
Keywords: (3GdfMhs